Does service employees' appearance affect the healthiness of food choice? - HUNEKE, Tabea: BENOIT (Institutional Knowledge at Singapore Management University, 2015)
Derived from previous research on social influence on food consumption and social comparison theory, this article examines the effect of service employees’ appearance on consumers’ food choice using an experimental study, involving a video manipulation and eye-tracking technique. The video shows a menu being proffered by a waitress whose degree of apparent healthiness varies (healthy, overweight, unhealthy lifestyle). The menu contains both healthy and unhealthy meal alternatives. The analysis of participants’ eye movements demonstrated that exposure to the overweight employee did not stimulate greater (i.e., earlier or longer) attention to unhealthy meal alternatives, whereas exposure to the employee who displayed an unhealthy lifestyle did. These findings have social and managerial implications: The postulated stigma according to which the presence of overweight others encourages unhealthy eating appears questionable. Service providers that might secretly hire according to body weight have no grounds to do so. In contrast, employees signaling an unhealthy lifestyle through their style choices prompt patrons to pay more attention to unhealthy meal alternatives. Food service providers might want to take this factor into consideration and actively manage the aspects that can be altered by simple measures.